2022
DOI: 10.5688/ajpe8603
|View full text |Cite
|
Sign up to set email alerts
|

Communication Apprehension Among Health Professions Students in Brazil

Abstract: Objective. To determine the levels of communication apprehension (CA) experienced by health students and compare them according to sex, age range, course, and academic year. Method. A cross-sectional study was conducted at a Brazilian university from December 2019 to May 2020 with dentistry, pharmacy, medicine, and nursing students, recruited by convenience sampling. The students were invited to answer a survey consisting of two sections: general characteristic and the Personal Report of Communication Apprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Further studies are needed to identify if there is any particularity in young people who apply for healthcare profession programmes that may increase anxiety in social contexts. Earlier contributions from cross-sectional studies also found moderate scores in communication apprehension in health students attending nursing [68,69], radiology [69], and pharmacy [68] programmes.…”
Section: Discussionmentioning
confidence: 81%
“…Further studies are needed to identify if there is any particularity in young people who apply for healthcare profession programmes that may increase anxiety in social contexts. Earlier contributions from cross-sectional studies also found moderate scores in communication apprehension in health students attending nursing [68,69], radiology [69], and pharmacy [68] programmes.…”
Section: Discussionmentioning
confidence: 81%
“…Individual factors : Gender was found to be positively associated with CA in 6 out of 9 studies that analyzed gender and CA, with female students reporting higher CA than male students in several studies (Anacleto de Araújo et al, 2022; A. M. Kerr & Thompson, 2022; Lang et al, 1998; McCroskey et al, 1983;O'Donnell, 1998; Pierce, 2016). Three out of 9 studies found no significant differences in CA based on gender (Hashemi et al, 2020; LaRochelle & Karpinski, 2016; Rogers & King, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The need for academics and program administrators to be aware of the anxieties students have regarding oral communication in general and the process of evaluation should also be given further consideration. Therefore, communication skills training programs to reduce students' apprehension are recommended (Araújo et al ., 2022; Hand, 2023). Universities and instructors must be able to help increase the students' SPCC as the higher the students' SPCC, the lower their CA tended to be.…”
Section: Implications For Practicementioning
confidence: 99%